Artificial Intelligence in cancer epigenomics: a review on advances in pan-cancer detection and precision medicine - Karishma Sahoo; Prakash Lingasamy; Masuma Khatun; Sajitha Lulu Sudhakaran; Andres Salumets; Vino Sundararajan; Vijayachitra Modhukur (Epigenetics & Chromatin)
Abstract DNA methylation is a fundamental epigenetic modification that regulates gene expression and maintains genomic stability. Consequently, DNA methylation remains a key biomarker in cancer research, playing a vital role in diagnosis, prognosis, and tailored treatment strategies. Aberrant methylation patterns enable early cancer detection and therapeutic stratification; however, their complex patterns necessitates advanced analytical tools. Recent advances in artificial intelligence (AI) and machine learning (ML), including deep learning networks and graph-based models, have revolutionized cancer epigenomics by enabling rapid, high-resolution analysis of DNA methylation profiles. Moreover, these technologies are accelerating the development of Multi-Cancer Early Detection (MCED) tests, such as GRAIL’s Galleri and CancerSEEK, which improve diagnostic accuracy across diverse cancer types. In this review, we explore the synergy between AI and DNA methylation profiling to advance precision oncology. We first examine the role of DNA methylation as a biomarker in cancer, followed by an overview of DNA profiling technologies. We then assess how AI-driven approaches transform clinical practice by enabling early detection and accurate classification. Despite their promise, challenges remain, including limited sensitivity for early-stage cancers, the black-box nature of many AI algorithms, and the need for validation across diverse populations to ensure equitable implementation. Future directions include integrating multi-omics data, developing explainable AI frameworks, and addressing ethical concerns, such as data privacy and algorithmic bias. By overcoming these gaps, AI-powered epigenetic diagnostics can enable earlier detection, more effective treatments, and improved patient outcomes, globally. In summary, this review synthesizes current advancements in the field and envisions a future where AI and epigenomics converge to redefine cancer diagnostics and therapy.